Some linguistic evidence of Quechua-Amazonian languages contact - Alanzo Sutta, Alicia N. (2002)
Linguistic research on the languages of the past by notable researchers has reached a greater peak in recent decades, thus contributing to the discovery of Amerindian languages, their approximate geographical location, as well as the possible contacts that would have occurred between them.The current evidence presented by history, archeology and linguistic studies in Peruvian territory demonstrates that, in ancient times, some societies would have moved great distances from their places of origin. These societies, along their journey, would have established exchange relationships with other populations different in language and culture.In the same way, the Inca society would have moved to a greater distance than is known, as demonstrated by the data written by travelers, missionaries and conquerors, which account for its advance to tropical regions that no longer constituted territory. inca. However, little is still known about the expansion of the Quechua language in the Amazon region during the development of the Inca Empire.Our research aims to show some terms that could constitute linguistic evidence of the Quechua - languages of the Peruvian Amazon contact that occurred before the arrival of Europeans.